2012
DOI: 10.1152/ajpgi.00453.2011
|View full text |Cite
|
Sign up to set email alerts
|

Consistent activation of the β-catenin pathway by Salmonella type-three secretion effector protein AvrA in chronically infected intestine

Abstract: Consistent activation of the ␤-catenin pathway by Salmonella typethree secretion effector protein AvrA in chronically infected intestine. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 57 publications
4
47
0
1
Order By: Relevance
“…In this model, Salmonella persistently promotes small intestinal and colonic epithelial proliferation in vivo over 10-27 weeks [180]. This study also showed that, under these conditions, Salmonella strains expressing AvrA enhance expression of Akt, potentiate phosphorylation and acetylation of β-catenin, induce β-catenin nuclear translocation, and increase transcription of target genes, which could be the explanation for increased proliferation.…”
Section: An Alphabetical Guide Tosupporting
confidence: 59%
“…In this model, Salmonella persistently promotes small intestinal and colonic epithelial proliferation in vivo over 10-27 weeks [180]. This study also showed that, under these conditions, Salmonella strains expressing AvrA enhance expression of Akt, potentiate phosphorylation and acetylation of β-catenin, induce β-catenin nuclear translocation, and increase transcription of target genes, which could be the explanation for increased proliferation.…”
Section: An Alphabetical Guide Tosupporting
confidence: 59%
“…Success of PD-1/PD-L1 blockade for treatment of melanoma depends in part on established T cell infiltration into tumors, which is disrupted by tumor-intrinsic WNT/β-catenin signaling [80]. Commensal gut bacteria can modulate WNT/β-catenin pathway and promote colon carcinogenesis [81, 82]. It is unknown if gut microbiota could extend such an influence to tumors outside the gastrointestinal tract, but it is conceivable that commensals at other sites (skin) could engage similar mechanisms to activate WNT/β-catenin in melanomas.…”
Section: Cancer Immunotherapy Is Influenced By Microbiotamentioning
confidence: 99%
“…The Wnt ligand receptor (Wnt5a-Fzd5) signaling in macrophages was reported to promote phagocytosis of bacteria and enhanced survival through lipid rafts with Rac1-phosphatidylinositol 3-kinase (PI3K)-IB kinase (IKK) activation (31). Others have demonstrated that Salmonella activates host ␤-catenin signaling; moreover, Salmonella type 3 secreted effectors AvrA and SopB can individually activate Wnt/␤-catenin signaling in epithelial cells, leading to increases of stem cells and proliferative cells and transdifferentiation of primed epithelial cells into M cells, respectively, to promote intestinal invasion (33)(34)(35)(36)(37). Wnt5a is known to activate canonical and noncanonical Wnt pathways and is linked to cytoskeletal modulation and proinflammatory cytokine activation, e.g., in human macrophages stimulated by Mycobacterium (38)(39)(40)(41)(42).…”
mentioning
confidence: 99%